(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study is to investigate the effectiveness of uterine artery Doppler velocimetry values to predict pregnancy in clomiphene citrate-induced intrauterine insemination cycles (IUI) in patients with polycystic ovary syndrome (PCOS). Materials and Methods: Patients with PCOS who applied to the infertility outpatient clinic between 01/06/2020 and 31/11/2021 were included in this prospective interventional study. For ovulation induction, patients used clomiphene citrate (CC) 50-150 mg daily between days 5 and 9 of the cycle. When at least one dominant follicle of 17 mm or larger was detected in serial transvaginal ultrasound controls, ovulation was triggered and IUI was performed 36 hours later. Uterine artery flow Resistance Index (RI), Pulsatility Index (PI), and systolic-diastolic ratio (S/D) were evaluated with Doppler ultrasound in all patients on the 3rd day of the cycle and the trigger day. Uterine artery Doppler values of the group that achieved pregnancy and those who could not conceive were compared as the main outcome of the study. Results: The study was designed on 56 cycles in which IUI can be performed after ovulation induction. In these 56 cycles, 10 pregnancies were obtained and the clinical pregnancy rate was 17.9%. The pregnant and non-pregnant groups were similar in terms of demographic characteristics, basal hormone levels, basal period and trigger day endometrial thickness, follicle number, and mean dominant follicle diameter (p>0.005). There was no significant difference in mean uterine artery Doppler values (PI, RI, and S/D) measured on the 3rd day of the cycle and the trigger day between the pregnant and non-pregnant groups (p>0.005). Conclusion: Considering the hormonal changes in stimulated cycles and the effect of CC itself on endometrial receptivity, we think that only uterine artery Doppler values are not effective in predicting pregnancy success in CC-induced IUI cycles in patients with PCOS.